If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4m = 10 + 5m Solving 9 + 4m = 10 + 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 9 + 4m + -5m = 10 + 5m + -5m Combine like terms: 4m + -5m = -1m 9 + -1m = 10 + 5m + -5m Combine like terms: 5m + -5m = 0 9 + -1m = 10 + 0 9 + -1m = 10 Add '-9' to each side of the equation. 9 + -9 + -1m = 10 + -9 Combine like terms: 9 + -9 = 0 0 + -1m = 10 + -9 -1m = 10 + -9 Combine like terms: 10 + -9 = 1 -1m = 1 Divide each side by '-1'. m = -1 Simplifying m = -1
| 141=o+3.3t | | (x+10)+2x+x=3000 | | 7x+14=-4x-18 | | 5x+10=-8x-20 | | 28.25=8+1.75x+8.00 | | -9-10j=9-8j | | -4+5s+3=7s-9 | | 4x^2y+28xy-8y=0 | | 2-10y=9-3y | | -3u+1=10-2u | | 7(10x+1)=70x-9 | | 27=3-2x | | 4(x+2)=4(x+10) | | 5-5-7k=-10k-10 | | 9.5+2x=32.7 | | x+2/2=8 | | 45+24x+3x^2=0 | | 8x-32-5x=37 | | 180=2x(3x+20) | | 14x+7y+21=0 | | -83+9x=25 | | 3(7x-4)= | | 7x+12=-5x-16 | | 8*2-5*3(-21)= | | 2(x+5)=2(x+11) | | 5x/4=-16 | | 8x-24=6x | | -48h^8/-8h^2 | | (x-10)=2x | | 5x+15=-3x-16 | | 83-5y=3 | | 8-6x=4x+49 |